Pertumbuhan Ikan Nila (Oreochromis niloticus) yang diberikan pakan kombinasi pelet dan maggot (Hermetia illucens) kering dengan presentasi berbeda - Sepang, Daniella A.; Mudeng, Joppy D.; Monijung, Revol D.; Sambali, Hariyani; Mokolensang, Jeffrie F. (e-Journal BUDIDAYA PERAIRAN, 2021)
This study aimed to determine the effect of providing a combination of natural feed maggots and pellets on the growth performance of Nile Tilapia and to ratio between maggots and pellets that promote growth of Nile Tilapia. The research was conducted from June to August 2020. The research method was using a completely randomized design (CRD) with 5 treatments and 3 replications with the following treatments: treatment A = 100% pellets, treatment B = 75% pellets and 25% maggots, treatment C = 50% pellets and 50% maggot, treatment D = 25% pellets and 75% maggot, treatment E = 100% maggot. The test fish used Nile Tilapia fingerling with average weighing 4 g / fish with density of 5 fish / container and maintained for 21 days. The containers used in this study were 15 plastic trays with a diameter of 40 cm and a height of 20 cm each with a water capacity of 15 liters. Growth performance data were Weight gain (WG), Specific growth rate (SGR), relative growth rate (SGR), feed convertion rate (FCR) and feed intake (FI). Based on the results of this study, it shows that the use of a combination of pellet and maggot feed as Nile tilapia juvenile has an effect on the growth performance of Nile tilapia so that maggot can be used as an alternative feed that has high nutritional content for tilapia fish cultivation. The treatment that gave the best growth effect on tilapia seeds was found at the dose of a combination of 50% pellet feed + 50% maggot, with Weight gain (5.5±1.1g), SGR (3.7±0.5%), RGR (139.4±53.4) and FCR (1.2±0.2)